(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2015)
Innovation in every field is an essential requisite. Forensic Accounting in the field of accounting is also considered to be essential due to the rapidly increasing number of frauds. Innovation in Accounting in terms of Forensic Accounting has taken place due to the increased number of corporate scams in an unmatchable speed. Frauds are spreading like a communicable disease by victimizing the corporate world in such a manner that the investors and economy as a whole finds difficult to re cover from it. In India the rate of rapid increase in the number of white collar crimes and frauds and lack of sufficient expertise to prevent these practices brings attention towards Forensic Accounting. Scams done by Ketan Parekh, Harshad Mehta and the Satyam Scam have shaken the economy and resulted in the increased demand of the Forensic Accoun tants so that preventive actions can be taken before it becomes a curse. Specialized knowledge in the field is a prerequisite for becoming a foren sic accountant. Some agencies are actively engaged in this field but there still exists a gap in the demand and supply of the forensic accountants. This paper makes an attempt to discuss the meaning, innovation and need of forensic accounting, hub of frauds and the working of forensic accoun tants to control it, prerequisites of a forensic accountant and the present status of forensic accounting and forensic accountant in India.